Edwards on God - Rehnman, Sebastian, author.
1 online resource
Keywords: "Jonathan Edwards is generally acknowledged as one of the foremost American philosophers. Edwards on God offers a historically informed philosophical analysis of his arguments for the existence and nature of God. The book begins with a characterization of Edwards's intellectual profile and philosophical theology. It then explicates and evaluates his arguments from the beginning of existence, design, 'being in general', virtue as benevolence, and his account of natural and moral divine attributes. There is no other such treatment of Edwards's metaphysics of divinity. This volume will be primarily relevant to philosophers, historians and theologians"--